The Readiness of Learning Processes during the New Normal Era of the Covid-19 Pandemic - Anwar Sewang; Muhammad Aswad (Indonesian Research Journal in Education |IRJE|, 2021)
Many studies have suggested that online learning that is so sudden and takes months is not effective. The unpreparedness of facilities and infrastructure becomes the main trigger in hindering the efficiency and effectiveness of the teaching and learning process. Parents and students miss face-to-face teaching and learning processes at school. This study aimed to investigate the readiness of parents and children for face-to-face learning during the “new normal” period. This study applied a quantitative design. The population in this study was the parents of students in Banggae, Majene, West Sulawesi. Samples were selected using the non-probability sampling technique; in this case, it was an accidental sampling. The instrument used to obtain data was a questionnaire. Data were then processed in three stages, namely editing, coding, and tabulating. Data were also analyzed with a descriptive analysis using a percentage formula. The results of this study indicated that parents were ready for face-to-face learning for their children at school. However, the children had not been able to get used to obeying the health protocols that have been established for the ‘new normal’ period.